Molecular Mechanics Studies of Antihypertensive Val-Tyr Dipeptide - AKVERDIEVA†, G.A.; GODJAYEV†‡, N.M.; AKYUZ*, S.; AKYUZ, T.; DOGAN, N.E. (Asian Journal of Chemistry, 2024)
The spatial structure of antihypertensive dipeptide, Valine-Tyrosine was investigated within molecular mechanics framework. It has been shown that the molecule has such a structural organization which does not exclude the realization of two types of conformation: folded and extended. The energy and geometrical parameters for the optimal conformations of dipeptide are obtained. The electronic characteristics for these structures were analyzed by quantum chemical calculations.